From obligation to action: unraveling the roles of social responsibility and prosocial tendency in shaping Chinese doctors’ vaccine hesitancy - Li, Xikun; Zhang, Yuwei; Li, Xinyang; Guo, Botang (Frontiers in Psychiatry, 2024)
Abstract Background: The hesitation of healthcare professionals towards vaccines is becoming increasingly concerning, potentially undermining public confidence in vaccination programs. This study aimed to investigate the relationship between social responsibility, Prosocial tendency, and vaccine hesitancy among Chinese doctors, and to identify demographic factors associated with vaccine hesitancy. Method: A cross-sectional survey was conducted among 976 Chinese doctors. Participants completed a questionnaire to assess their sense of social responsibility, Prosocial tendency, and vaccine hesitancy. Demographic information, including age, gender, and marital status, was also collected. Correlation and mediation analyses were conducted to examine the relationships between the main variables. Results: Social responsibility was negatively correlated with vaccine hesitancy (r=-0.564, P<0.01) and positively correlated with Prosocial tendency (r=0.519, P<0.01). Prosocial tendency was negatively correlated with vaccine hesitancy (r=-0.505, P<0.01) and partially mediated the relationship between social responsibility and vaccine hesitancy. Younger age, female gender, and unmarried status were associated with higher levels of vaccine hesitancy. Conclusion: This study emphasized the important role of social responsibility and Prosocial tendency in reducing vaccine hesitancy among Chinese doctors. The findings suggest that interventions aimed at fostering a strong sense of social responsibility and promoting Prosocial tendency may effectively address vaccine hesitancy in this population. Additionally, targeted interventions focusing on young, female, and unmarried doctors may be necessary.